Food Policy for All: Inclusion of Diverse Community Residents on Food Policy Councils. - McCullagh, Molly. (2017)
Abstract: Food Policy Councils (FPCs) are committees of food system actors that propose policy and programming changes to strengthen a region's economy, environment, and community as they relate to the food system. Nearly 150 FPCs are operating at various capacities in American and Canadian cities, regions, and states. FPCs generally operate within the Community Food Security framework, which emphasizes cross-sector collaboration on community-level and systems-oriented solutions. There has been little research related to how community residents who are most impacted by social inequities or who are most at risk for food insecurity are involved in FPC activities. This research is focused on assessing why and how FPCs include diverse community residents (here defined as low-income consumers, women, mothers, seniors, youth, and people of color) in their policy and programming work. Examples drawn from interviews with a variety of FPCs shed light on current efforts of inclusion and inspire suggestions for improvement.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Julian Agyeman, and Hugh Joseph.; Keywords: Public policy, Agriculture, and Environmental justice.